New nano-geopolymer cement system improves wellbore integrity upon acidizing job: Experimental findings - Ridha, S. (Society of Petroleum Engineers, 2015)
Acid stimulation job is one of alternative technique used to improve well productivity. However, improper usage and design of this method may pose problems to the cements surrounding the perforation area of the well and it may lead to well integrity problems. Therefore a good the cement system must exhibit the physical and chemical properties that are not reactive to most types of acids used in acidizing job. This paper developed a new nano-geopolymer cement containing portions of nano-scales of silica, flyash and alkaline liquid under geopolimerization process. The experimental work is simulated under downhole conditions at pressure up to 4000 psi and temperature up to 120Â°C. Strength buildup profile was analyzed using Ultrasonic Cement Analyzer. This research also exposed cement samples into acidic environment of mixed HCL and HF with the ratio of 12 and 3 up to 24 hours. Curing times conditioned to be varied along the test to better describe the chemical and mechanical changing due to acid. Advanced Scanning Electron Microscopy (SEM) is used to describe microstructure deformartions of cement samples. Compared to class G cement, pure geopolymer and nano-SiO2 geopolymer cement have better acid resistance as they experienced less strength loss. It is found that nano-SiO2 possessed the tendency on enhancing pure geopolymer cement property through the strength test. Although the strength degraded, the strength loss is not as much as class G and high initial strength value of nano-SiO2 geopolymer cement gives benefit in maintaining high strength value after acidizing. Sample NG1 with 1 nano-SiO2 obtained the highest strength value and minor crack after 24 hours acid exposure. The result shows that the new cement system can improve the wellbore integrity by resistingacid alteration and penetration upon acidizing job. At the same time the CO2 emissions from producing conventional API cement can be eliminated by the new nano-geopolymer cement. Copyright 2015, Society of Petroleum Engineers.